Primary amenorrhea due to Asherman syndrome with dermoid cyst excision - Mishra, Shruti R.; Mishra, Dhyey R.; Moruskar, Aditya S.; Desai, Gaurav S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Primary amenorrhea is less common than secondary amenorrhea. It can be caused by various anatomical, genetic, or hormonal factors during the development of the reproductive organs. Congenital absence of the endometrium or sclerotic endometrium is a very rare cause of primary amenorrhea. We describe a case of sclerotic or non-functional endometrium in the context of normal female karyotype 46 XX and recurrent dermoid cyst.